2006
DOI: 10.1097/00004703-200604000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy, Outcome Expectations, and Diabetes Self-Management in Adolescents with Type 1 Diabetes

Abstract: The goal of this research was to develop and evaluate measures of adolescent diabetes management self-efficacy and outcome expectations that reflect developmentally relevant, situation-specific challenges to current diabetes regimens. Self-efficacy for diabetes management, expected outcomes of adherence, adherence to the diabetes regimen, and glycemic control were assessed in 168 adolescents (ages 10-16 years) with type 1 diabetes. Factor analyses indicated a single scale for self-efficacy and two distinct fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
232
7
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 258 publications
(261 citation statements)
references
References 20 publications
11
232
7
11
Order By: Relevance
“…The pathway from higher diabetes self-efficacy to greater adherence and lower HbA1c is consistent with daily diary work linking daily self-efficacy to adherence and blood glucose control (Fortenberry, Butler, Butner, Berg, Upchurch, & Wiebe, 2009). Furthermore, this pathway is consistent with the social-cognitive theory underlying self-efficacy (e.g., Iannotti et al, 2006), where confidence in one's ability to complete diabetes-management tasks in the face of difficulties should be evident in behavioral aspects of diabetes management. These results point to self-efficacy as an important benefit associated with a high quality parent-adolescent relationship, a factor that may be especially crucial for young adolescents who are beginning to manage their diabetes more independently from their parents.…”
Section: Discussionsupporting
confidence: 72%
“…The pathway from higher diabetes self-efficacy to greater adherence and lower HbA1c is consistent with daily diary work linking daily self-efficacy to adherence and blood glucose control (Fortenberry, Butler, Butner, Berg, Upchurch, & Wiebe, 2009). Furthermore, this pathway is consistent with the social-cognitive theory underlying self-efficacy (e.g., Iannotti et al, 2006), where confidence in one's ability to complete diabetes-management tasks in the face of difficulties should be evident in behavioral aspects of diabetes management. These results point to self-efficacy as an important benefit associated with a high quality parent-adolescent relationship, a factor that may be especially crucial for young adolescents who are beginning to manage their diabetes more independently from their parents.…”
Section: Discussionsupporting
confidence: 72%
“…Self-efficacy and outcome expectations. The Self-Efficacy for Diabetes SelfManagement scale and the Outcome Expectations of Diabetes Self-Management Positive and Negative scales (32) were administered at baseline and each follow-up. Self-Efficacy for Diabetes Self- …”
Section: Educational Controlmentioning
confidence: 99%
“…In two studies conducted in different times, SEQ-C and self-respect were low for adolescents diagnosed with DM Type 1 and who didn't show any compliance with the disease. It was stated that efforts to increase self-respect and SEQ-C might also increase the level of compliance with the disease and treatment and would bring success 28,29 . In our study, perception of SEQ-C of students with CHC was found similar to healthy students.…”
Section: Discussionmentioning
confidence: 99%